THE ROLE OF DIGITAL TOOLS IN BIOSTATISTICS AND MEDICAL DATA ANALYSIS IN HIGHER MEDICAL EDUCATION (KIUT Publication, 2025)
In 2020, through Resolution 58.28, the World Health Assembly called on member states to consider long-term planning for eHealth and to develop and implement strategic plans for electronic health services. The development of information and communication infrastructure is aimed at promoting equitable and affordable health technologies and ensuring universal access to their benefits. Countries and stakeholders were urged to direct their efforts consistently towards creating eHealth systems. Over 120 member states, including low- and middle-income countries, have developed such strategies.